DNA extraction methods from vicuña fecal samples (Vicugna vicugna mensalis) - Maturrano H., Lenin (2012)
At present, the use of DNA extracted from non-invasive samples, especially feces, is common practice in the discipline of conservation genetics. Even though DNA analysis is often difficult mainly due to the composition and preservation of feces has been shown in many species with the development of suitable extraction methods is possible to maximize the reliability and effectiveness of such procedures. The objective of this study has been optimization of a protocol for the extraction of DNA from vicuña feces (Vicugna vicugna mensalis), species classified as Near Threatened in Peru, in order to obtain DNA of sufficient quality for molecular analysis. A total of 51 samples were taken from vicuña dung piles in two communities located 4600 meters above sea level in the dry Puna ecosystems of the regions of Junin and Moquegua between August and September 2008. After observing defecation, samples were collected immediately, preserved in ethanol and transported to the laboratory for DNA extraction. Modification of the protocol of the QIAamp ® DNA Stool Mini Kit (QIAGEN) to include an extended period of vigorous shaking was found to producer higher quality DNA than was obtained using both the kit protocol and PCI (Phenol/chloroform/isoamyl alcohol). The amount of extracted DNA was visualized using horizontal agarose gel electrophoresis, and the quality was tested analyzing microsatellite markers LCA 19 and YWLL 46 on polyacrylamide gels. Although DNA was obtained by all three methods, only the modified protocol produced DNA of sufficient quality for use in molecular analyses.